STRUCTURAL MODEL OF PEDAGOGICAL TRAINING OF STUDENTS TO PREVENTIVE ACTIVITY WITH STUDENTS PRIMARY SCHOOL - L.Yu. Puzanova (Academy of Cognitive and Natural Sciences, 2007)
In this article it is theoretically grounded the structure model of pedagogical raining the students ' preventive activity with the pupils of the primary school and rended concrete its structure components of, realization of which positively gives influence on the quality of preparation of the pedagogical specialists.